Intracranial Pressure Elevation 24 h after Ischemic Stroke in Aged Rats Is Prevented by Early, Short Hypothermia Treatment - Murtha, Lucy A.; Beard, Daniel J.; Bourke, Julia T.; Pepperall, Debbie; McLeod, Damian D.; Spratt, Neil J. (Frontiers in Aging Neuroscience, 2016)
Stroke is predominantly a senescent disease, yet most preclinical studies investigate treatment in young animals. We recently demonstrated that short-duration hypothermia-treatment completely prevented the dramatic intracranial pressure (ICP) rise seen post-stroke in young rats. Here, our aim was to investigate whether a similar ICP rise occurs in aged rats and to determine whether short-duration hypothermia is an effective treatment in aged animals. Experimental Middle Cerebral Artery occlusion (MCAo - 3 hour occlusion) was performed on male Wistar rats aged 19-20 months. At one hour after stroke-onset, rats were randomized to 2.5 hours hypothermia-treatment (32.5 °C) or normothermia (37 °C). ICP was monitored at baseline, for 3.5 hours post-occlusion, and at 24 hours post-stroke. Infarct and edema volumes were calculated from histology. Baseline pre-stroke ICP was 11.2 ± 3.3 mmHg across all animals. Twenty-four hours post-stroke, ICP was significantly higher in normothermic animals compared to hypothermia-treated animals (27.4 ± 18.2 mmHg vs. 8.0 ± 5.0 mmHg, p = 0.03). Infarct and edema volumes were not significantly different between groups. These data demonstrate ICP may also increase 24 hours post-stroke in aged rats, and that short-duration hypothermia treatment has a profound and sustained preventative effect. These findings may have important implications for the use of hypothermia in clinical trials of aged stroke patients.